Xq22 deletion involving TCEAL1 in a female patient with early-onset neurological disease trait - Keiko Shimojima Yamamoto; Yusuke Itagaki; Kazuki Tanaka; Nobuhiko Okamoto; Toshiyuki Yamamoto (Human Genome Variation)
Abstract A 3.5-Mb microdeletion in Xq22 was identified in a female patient with early-onset neurological disease trait (EONDT). The patient exhibited developmental delay but no hypomyelination despite PLP1 involvement in the deletion. However, the clinical features of the patient were consistent with those of TCEAL1 loss-of-function syndrome. The breakpoint junction was analyzed using long-read sequencing, and blunt-end fusion was confirmed.